Stimulation of bacteriophage T4 middle transcription by the T4 proteins MotA and AsiA occurs at two distinct steps in the transcription cycle - Adelman, Karen (The National Academy of Sciences, 1998)
The bacteriophage T4 encodes proteins that are responsible for tightly regulating mRNA synthesis throughout phage development in Escherichia coli. The three classes of T4 promoters (early, middle, and late) are utilized sequentially by the host RNA polymerase as a result of phage-induced modifications. One such modification is the tight binding of the T4 AsiA protein to the σ(70) subunit of the RNA polymerase. This interaction is pivotal for the transition between T4 early and middle transcription, since it both inhibits recognition of host and T4 early promoters and stimulates T4 middle mode synthesis. The activation of T4 middle transcription also requires the T4 MotA protein, bound specifically to its recognition sequence, the “Mot box,” which is centered at position −30 of these promoters. Accordingly, the two T4 proteins working in concert are sufficient to effectively switch the transcription specificity of the RNA polymerase holoenzyme. Herein, we investigate the mechanism of transcription activation and report that, while the presence of MotA and AsiA increases the initial recruitment of RNA polymerase to a T4 middle promoter, it does not alter the intrinsic stability of the discrete complexes formed. In addition, we have characterized the RNA polymerase-promoter species by UV laser footprinting and followed their evolution from open into initiating complexes. These data, combined with in vitro transcription assays, indicate that AsiA and MotA facilitate promoter escape, thereby stimulating the production of full-length transcripts.